Fungicide pyraclostrobin affects midgut morphophysiology and reduces survival of Brazilian native stingless bee Melipona scutellaris - da Costa Domingues, Caio Eduardo [UNESP]; Bello Inoue, Lais Vieira [UNESP]; da Silva-Zacarin, Elaine Cristina Mathias; Malaspina, Osmar [UNESP] (Elsevier, 2020)
Native stingless bees are key pollinators of native flora and important for many crops. However, the loss of natural fragments and exposure to pesticides can hinder the development of colonies and represent a high risk for them. Nevertheless, most studies are conducted with honeybees and there are not many studies on native species, especially in relation to the effects of fungicides on them. Therefore, the objective of this paper is to evaluate the effects of sublethal concentrations of pyraclostrobin, on Melipona scutellaris forager workers. These Brazilian native stingless bees were submitted to continuous oral exposure to three concentrations of pyraclostrobin in sirup: 0.125 ng a.i./µL (P1), 0.025 ng a.i./µL (P2), and 0.005 ng a.i./µL (P3). Histopathological and histochemical parameters of midgut, as well as survival rate were evaluated. All concentrations of fungicide showed an increase in the midgut lesion index and morphological signs of cell death, such as cytoplasmic vacuolizations, presence of atypical nuclei or pyknotic nuclei. Histochemical analyzes revealed a decreased marking of polysaccharides and neutral glycoconjugates both in the villi and in peritrophic membrane in all exposed-groups in relation to control-groups. P1 and P2 groups presented a reduction in total protein marking in digestive cells in relation to control groups. As a consequence of alteration in the midgut, all groups exposed to fungicide showed a reduced survival rate. These findings demonstrate that sublethal concentrations of pyraclostrobin can lead to significant adverse effects in stingless bees. These effects on social native bees indicate the need for reassessment of the safety of fungicides to bees.
Keywords: Ecotoxicology; Meliponini; Midgut; Pyraclostrobin; Sublethal effects